Conceptual development and simulation of a PLC-based greenhouse climate regulation system using synthetic data - Ramírez Baquerizo, Franklin Cesar; Carrasco Agraces, Oscar; Pincay-Bohórquez, Freddy; Pilacuan-Bonete, Luis (EASI: Engineering and Applied Sciences in Industry, 2026)
This paper presents the conceptual design and simulation of an automated greenhouse climate control system aimed at melon cultivation in the coastal region of Ecuador. The proposal is based on the use of programmable logic controllers (PLC) and a human–machine interface (HMI), developed entirely within a simulation environment using synthetic data and predefined engineering assumptions. The system is designed to regulate critical environmental variables such as air temperature, relative humidity, and soil moisture through a structured and modular control logic implemented in Ladder language. The adopted methodology prioritizes logical and functional validation of the system without relying on physical sensors or field testing, allowing the evaluation of operational coherence under different simulated environmental scenarios. The results demonstrate stable and consistent system behavior, with appropriate automatic responses to conditions of thermal and water stress. Additionally, the proposed control strategy shows potential improvements in water use efficiency and greenhouse microclimate stability. This study represents a preliminary, non-experimental contribution that provides a structured foundation for future stages involving physical implementation, field validation, and the integration of advanced technologies in agro-industrial greenhouse automation systems.